Patriots in "Kala Pani?": Writing subaltern resistance into the nationalist memory - Zehmisch, Philipp (Cultural histories of India, 2020)
The widely known allegory of “Kala Pani” gained particular traction in the first decades of the twentieth century when narratives and reports about the
Gesehen am 26.05.2021